Effects of different saliva pH on hybrid composite resin surface roughness - Nirawati Pribadi; Adioro Soetojo (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: Currently, hybrid composite resin is the mostly used filling material to restore esthetic and function. During function, this material is in contact with various pH from food consumption, which is acidic and alkali which may effect the physical properties of composite resin, including surface roughness. Purpose: The research was conducted to determine the effect of pH in saliva on surface roughness of hybrid composite resin. Methods: This research used artificial saliva and composite resin samples divided into 3 groups based on different pH of immersion (pH 4, pH 7 and pH 10) for 30 days. Results: There were significant differences (p > 0.05) among those three treatment groups of hybrid composites soaked in artificial saliva with different pH for 30 days. And, with LSD test it is also known that there were significant differences between the artificial saliva with pH 4 and pH 7, whereas there was no significant difference between pH 4 and pH 10 and between pH 7 and pH 10. Conclusion: It can concluded that the changes of salivary pH affect the surface roughness of the hybrid composite resin. Acidic pH has increase the surface roughness of hybrid composite resin, whereas alkaline pH has no effects on the surface roughness of hybrid composite resin.Latar belakang: Saat ini tumpatan komposit merupakan bahan tumpatan yang paling sering digunakan untuk memperbaiki estetik dan fungsi. Dalam rongga mulut, bahan ini kontak dengan berbagai macam pH dari konsumsi makanan, baik asam maupun basa yang dapat mempengaruhi perubahan sifat fisik resin komposit, diantaranya yaitu kekasaran permukaan. Tujuan: Penelitian ini dilakukan untuk mengetahui tentang efek pH saliva terhadap kekasaran permukaan tumpatan resin komposit hybrid. Metode: Penelitian ini menggunakan saliva buatan yang dibagi dalam 3 kelompok sampel yaitu masing-masing dengan perendaman pH yang berbeda (pH 4, pH 7 dan pH 10)selama 30 hari. Hasil: Terdapat perbedaan yang bermakna (p > 0,05) antara kelompok perlakuan komposit hybrid yang telah direndam saliva buatan dengan berbagai pH selama 30 hari. Uji LSD menunjukkan adanya perbedaan yang signifikan antara perendaman pada saliva buatan antara pH4 dengan pH 7, sedangkan perbedaan yang tidak signifikan antara pH4 dengan pH 10 dan pH 7 dengan pH 10. Kesimpulan: Dapat disimpulkan bahwa perubahan pH saliva berpengaruh terhadap kekasaran permukaan resin komposit hybrid, pH asam meningkatkan kekasaran permukaan resin komposit hybrid, sedangkan pH basa tidak berpengaruh terhadap kekasaran permukaan resin komposit hybrid.